Tuberculosis disease perceptions and healthcare-seeking behavior of household contacts among Raglai Ethnic Group in Khanhvinh District, Khanhhoa Province, Vietnam 2007-2008 - Ho Ta Phuong
Participants: 120 adults household contacts of 84 Raglai patients with PTB listed in active case files during the two years 2007-2008 from Khanhvinh district, Khanhhoa province, Vietnam were included in this study. Objectives: The general objective of this study was to explore the TB related healthcare-seeking behavior of the household contacts of Raglai PTB patients; and to determine its possible relationship with factors such as demographic characteristics of household contacts, knowledge about TB and TB program, attitudes associated with TB, physical factors, and language used in information, education and communication (IEC). Design: an analytical, cross-sectional study with historical control. Instrument: A Vietnamese-Raglai questionnaire adapted and modified from two similar previous studies in Vietnam. Data collection methods: letters of request to participate in the study were handed over to and then informed consent were collected from the household contact. Interviewers visited the respondents' homes to take interviews. One interviewer asked the questions to the participant while the other one filled up the questionnaire based on the respondents' answer. The data were collected between October and December 2008. Data analysis: completed questionnaires were coded and the quantitative data were computed using the Stata/SE version 10.0. Content analysis was used to analyze the responses to the open-ended qualitative questions. Results: 1. Nearly half (46.7%) of the respondents was illiterate. 83.4% of subjects were living below poverty line.2. The level of knowledge about tuberculosis was fairly good. However, lack of specific knowledge about TB continues to be common in the community. 3. The attitude of household contacts was generally good. However, TB related stigma continues to be prevalent in the study area. 4. Language used in IEC resulted in a greater knowledge transmission through posters than through other educational modes. Given that TV broadcasting using Raglai language is limited, it was not surprising that television was less a source of information about TB. Furthermore, radio was not availed of because there was no Raglai language program at all on radio. 5. TB related healthcare-seeking behavior was positively affected by status of the treatment partner and levels of general knowledge about TB; negatively affected by lack of means of transportation, high degree of fear about contracting TB, and the low level of understanding written Kinh language related to IEC. 6. The availability of free medical care from state health insurance was the most important factor that facilitated healthcare-seeking behavior of Raglai household contacts. Factors that hampered the healthcare-seeking behavior among contacts included lack of time, refusal to leave work, and long distance from homes to the nearest commune center. Recommendations: 1. Health education and communication about TB applied on the Raglai population in Khanhvinh district should be continuously improved, in which the contents of education programs should pay special attention to:increase community awareness of the cause, the mode of TB transmission, the right measures of TB prevention, and the importance of seeking health care when having symptoms suggesting TB; encourage social support and practice right measures of TB prevention, making known the important role of social support to TB control; encourage people to practice positive behavior related to TB by presenting themselves at health centers when they have symptoms suggestive of TB. 2. Health education and communication should be conducted through various channels at the same time, in which television, posters and health care professionals should be prioritized. Television broadcasting in Raglai language about TB information should be allocated more time. Health care workers in Raglai population should learn to communicate well with patients in Raglai language.3. Further studies should be done to evaluate the effectiveness of health education through religious churches in communities. 4. Evaluation for the effectiveness of communication activities on tuberculosis control should be conducted so that we can draw experiences and to better program activity planning. 5. Improvement in level of education and socio-economic conditions of the population is a long-term solution challenging the local authority and the government.